2019
DOI: 10.16943/ptinsa/2019/49718
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural Microbiology Research Progress in India in the New Millennium

Abstract: The research efforts in microbiology over last two decades have focussed on assessing the microbial diversity in various soil types and cropping systems in all agro-eco-regions, including extreme environments resulting in creation of a vast repository of microorganisms, free living and endophytes. A marked departure from the past is their identification by both conventional and molecular methods, resulting in discovery of many novel species. The effects of various soil and agronomic management practices were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 62 publications
1
15
0
Order By: Relevance
“…Mineral fertilization reduces plant nodulation (Heath et al, 2010; Regus et al, 2016) and symbiotic e ciency (Gordon et al, 2016; Heath & Ti n, 2007; Rao et al, 2019; Weese et al, 2015) because it is energetically cheaper for plants to reduce ammonium and nitrate than to x N 2 , leading to a reduction on the presence and diversity of rhizobia over time (da-Silveira-Cardillo et al, 2019; Moreira et al, 2006). In the other hand, soil organic amendments, such as manure, increase the abundance and diversity of microorganisms and rhizobia (Li et al, 2022; Malhotra et al, 2015; Rao et al, 2019), promoting a greater plant nodulation(Herencia et al, 2020), as in our results (Fig.1and Fig.2).Consequently, the use of these agrochemicals leads to a loss of abundance and diversity in the soil microbiome(Rao et al, 2019), as well as of rhizobia (Silva Neto et al, 2013; Weese et al, 2015), as we observed in the conventional management plots with reduction in plant nodulation (Table…”
supporting
confidence: 74%
See 1 more Smart Citation
“…Mineral fertilization reduces plant nodulation (Heath et al, 2010; Regus et al, 2016) and symbiotic e ciency (Gordon et al, 2016; Heath & Ti n, 2007; Rao et al, 2019; Weese et al, 2015) because it is energetically cheaper for plants to reduce ammonium and nitrate than to x N 2 , leading to a reduction on the presence and diversity of rhizobia over time (da-Silveira-Cardillo et al, 2019; Moreira et al, 2006). In the other hand, soil organic amendments, such as manure, increase the abundance and diversity of microorganisms and rhizobia (Li et al, 2022; Malhotra et al, 2015; Rao et al, 2019), promoting a greater plant nodulation(Herencia et al, 2020), as in our results (Fig.1and Fig.2).Consequently, the use of these agrochemicals leads to a loss of abundance and diversity in the soil microbiome(Rao et al, 2019), as well as of rhizobia (Silva Neto et al, 2013; Weese et al, 2015), as we observed in the conventional management plots with reduction in plant nodulation (Table…”
supporting
confidence: 74%
“…1-2) ( We also found lower abundance and diversity in the soil microbiome in conventional managements plots even before sowing and under irrigated conditions (Table 3). This would be related to the practices and agrochemicals used in conventional agriculture (Rao et al, 2019), since the two sampled agricultural soils, conventional and organic, had similar climatic conditions and both presented similar cropping histories and similar soil characteristics (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…reported that variation in days taken to flowering is attributed to genetic makeup of various germplasm lines. Moreover, due to favorable climatic conditions there is more dry matter accumulation which favors early flowering in marigold (Rao and Reddy, 2002).…”
Section: Evaluation Of Genotypesmentioning
confidence: 99%
“…Only by identifying the primary areas of research and development within distinct agricultural sectors can the concerns of overpopulation and food security be addressed (Singh et al, 2016). As a result, over the last two decades, agricultural microbiology research has focused on assessing microbial diversity in a variety of soil types and cropping systems across all agro-ecoregions, including extreme environments, resulting in the creation of a vast repository of microorganisms, free-living and endophytes (Rao et al, 2019). The use of microorganisms, their enzymatic machinery, or their products in bioremediation technology gives hope for a long-term, cost-effective technique of mitigating and turning contaminants harmless through natural biological processes.…”
mentioning
confidence: 99%
“…To target the uncharted depths of microbial existence and persistence, microbes especially bacteria have been isolated from various chemically contaminated sites (Mukherjee et al ., 2013; Singh et al ., 2013; Kumar et al ., 2015; Verma et al ., 2015) and extremophilic areas (Dwivedi et al ., 2015; Sharma et al ., 2018; Sood et al ., 2021a). Another major impact of microbiological research in India is on the identification of rapid methods of soil biological health assessment, microbial technology for rapid in situ and ex situ residue, and waste breakdown (Rao et al ., 2019). Indian microbiologists are taking advantage of the technological advancements in DNA sequencing and computational biology that have opened new fields of inquiry, particularly in genomics and metagenomics (Kumar et al ., 2013; Sangwan et al ., 2014; Verma et al ., 2014; Kumar et al ., 2017; Nagar et al ., 2020).…”
mentioning
confidence: 99%